2019
DOI: 10.1007/s12036-019-9583-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical detection of a GMRT-detected candidate high-redshift radio galaxy with 3.6-m Devasthal optical telescope

Abstract: We report optical observations of TGSS J1054+5832, a candidate high-redshift (z = 4.8 ± 2) steepspectrum radio galaxy, in r and i bands using the faint object spectrograph and camera mounted on 3.6-m Devasthal Optical Telescope (DOT). The source previously detected at 150 MHz from Giant Meterwave Radio Telescope and at 1420 MHz from Very Large Array has a known counterpart in near-infrared bands with K-band magnitude of AB 22. The source is detected in i-band with AB24.3 ± 0.2 magnitude in the DOT images prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This indicates that stars fainter than 24 mag in B filter have been detected with an accuracy of ∼ 0.2 mag in an effective exposure time of 20 min. Using the FOSC, a 24.5 mag object has been detected with an accuracy of 0.2 mag in one hour of integration time in i−band (Omar et al 2019b). The detection limits at optical wavelengths are at par with the performance of other 3.6 meter aperture optical telescopes located at good observing sites.…”
Section: Capabilities At Optical Wavelengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that stars fainter than 24 mag in B filter have been detected with an accuracy of ∼ 0.2 mag in an effective exposure time of 20 min. Using the FOSC, a 24.5 mag object has been detected with an accuracy of 0.2 mag in one hour of integration time in i−band (Omar et al 2019b). The detection limits at optical wavelengths are at par with the performance of other 3.6 meter aperture optical telescopes located at good observing sites.…”
Section: Capabilities At Optical Wavelengthsmentioning
confidence: 99%
“…The detection limits at optical wavelengths are at par with the performance of other 3.6 meter aperture optical telescopes located at good observing sites. The night sky brightness values are estimated to be 21 and 20.4 (mag arcsec −2 ) in the r and i bands respectively (Omar et al 2019b). These numbers indicate that the night sky at Devasthal is dark and it has not degraded since late 1990s when Devasthal site characterization was carried out.…”
Section: Capabilities At Optical Wavelengthsmentioning
confidence: 99%
“…ADFOSC has the capability of obtaining deep images with a precision of about 0.2 mag for a 24 magnitude object in about 1 hour of integration. Recently, Omar et al (2019b) reported the DOT i-band detection of a high-redshift candidate radio galaxy discovered from GMRT data (see Figure 4). Therefore, searches for such red objects in the i and z bands with ADFOSC are expected to be as fruitful as that in the NIR bands using TIRCAM-2.…”
Section: Synergy With Gmrt and Other Radio Telescopesmentioning
confidence: 99%
“…Figure 2 shows the pictures of the as-built telescope along with back-end instruments being used for regular observations. For observations at optical wavelengths, 4K × 4K CCD IMAGER (Pandey et al 2018) and Faint Object Spectrograph and Camera (FOSC) (Omar et al 2012(Omar et al , 2019a are used while TIRCAM2, acronym for TIFR Near Infrared Imaging Camera-II, is used in NIR region. The 3.6-m DOT was used for detailed characterisation of these instruments as well as for some science programs, which included photometric and spectroscopic study of supernovae, optical transient events, AGNs and quasars, galactic star forming regions, and distant galaxies.…”
Section: Introductionmentioning
confidence: 99%